2014
DOI: 10.1364/oe.22.032308
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural variation of memory colors of familiar objects

Abstract: Abstract:The effect of cross-regional or cross-cultural differences on color appearance ratings and memory colors of familiar objects was investigated in seven different countries/regions -Belgium, Hungary, Brazil, Colombia, Taiwan, China and Iran. In each region the familiar objects were presented on a calibrated monitor in over 100 different colors to a test panel of observers that were asked to rate the similarity of the presented object color with respect to what they thought the object looks like in reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
(40 reference statements)
4
29
0
Order By: Relevance
“…From Table 1, it is clear that the inter-observer STRESS and RMSE values are very similar for all meat types. The intra-and inter-observer STRESS values are also similar to the values reported in a study on cross-cultural variation in memory colors 16 and indicate good observer consistency and agreement. The intra-observer RMSE values show that observers are capable of reporting the same rating within about one scale unit.…”
Section: Observer Variabilitysupporting
confidence: 80%
“…From Table 1, it is clear that the inter-observer STRESS and RMSE values are very similar for all meat types. The intra-and inter-observer STRESS values are also similar to the values reported in a study on cross-cultural variation in memory colors 16 and indicate good observer consistency and agreement. The intra-observer RMSE values show that observers are capable of reporting the same rating within about one scale unit.…”
Section: Observer Variabilitysupporting
confidence: 80%
“…These results indicate that natural and other familiar objects always tend to be perceived in their typical memorized color. By providing cues to the visual system, which may serve as an internal reference, memory colors are therefore considered to play a crucial role for the mechanisms of color constancy and color appearance under varying illumination conditions as well as for color reproduction and color rendering applications …”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that natural and other familiar objects always tend to be perceived in their typical memorized color. By providing cues to the visual system, which may serve as an internal reference, memory colors are therefore considered to play a crucial role for the mechanisms of color constancy and color appearance under varying illumination conditions 1,9,[15][16][17] as well as for color reproduction [18][19][20][21][22][23][24][25][26] and color rendering applications. [27][28][29][30][31][32][33] Because of their potential use as an internal reference in the assessment of color appearance and color quality, first experiments aiming to explore the characteristics of memory colors quantitatively were performed by Newhall et al 3 and Bartleson.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of cross‐cultural studies have found that culture plays a role in social behavior and sensory perception (Barlas & Obhi, ; Goetz, Keltner, & Simon‐Thomas, ; Smet et al, ; Sorokowska, Sorokowski, & Frackowiak, ). Recent publications have shown that the taste sensitivities and evaluations vary among people with different cultural backgrounds, or even with different locations (Baharuddin & Sharifudin, ; Calderon, Angulo, O'mahony, & Wichchukit, ).…”
Section: Introductionmentioning
confidence: 99%